Literatur und Unabhängigkeit Transatlantische Verflechtungen bei fray Servando Teresa de Mier (1763-1827) - Kraume, Anne (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2023)
The study writes a cultural history of transatlantic relations on the late 18th and 19th centuries. Using the example of the Neo-Spanish Dominican fray Servando Teresa de Mier (1763-1827), it examines how Hispanic American writers of the transition between the early modern and modern period transgressed geographic, cultural, and discursive border regimes, thereby preparing the political and literary independency of the previous Spanish colonies.